Military Modernisation and Civil-Military Relations in Indonesia
XXIII, 142 p. 8 illus., 7 illus. in color.
Keywords: This book critically examines the development of the post-authoritarian Indonesian National Armed Forces’ (Tentara Nasional Indonesia) military modernisation agenda and its impact towards civil-military relations. It offers an original analysis on various and interrelated subjects related to Indonesia’s defence development, i.e., arms build-up, organisational development, conduct of military operations other than war, defence diplomacy, and defence economy. These analyses offer a better understanding on the role played by the Indonesian military in undertaking a modernisation agenda and sustaining its political influence over the non-defence sphere simultaneously. Each chapter contributor aims to examine the most recent development pertaining to their topic and the influence of civil-military dynamics on their subject matter. The book will be of interest to undergraduate and graduate students, professionals, and experts on Southeast Asian politics, defence studies, security studies, and civil-military relations. Muhamad Haripin is a researcher at the Research Centre for Politics – National Agency for Research and Innovation (Badan Riset dan Inovasi Nasional/BRIN), Indonesia. Adhi Priamarizki is a Research Fellow at Indonesia Programme, S. Rajaratnam School of International Studies (RSIS), Nanyang Technological University, Singapore. Leonard C. Sebastian is Senior Fellow at the Indonesia Programme, Institute of Defence and Strategic Studies (IDSS) at the S. Rajaratnam School of International Studies (RSIS) at Nanyang Technological University (NTU).